War Games redux? Cyberthreats, US–Russian strategic stability, and new challenges for nuclear security and arms control. Issue 2 (2nd April 2016) - Futter, Andrew
ABSTRACT: Some 30 years since the release of the Hollywood blockbuster War Games, the possibility that hackers might break into nuclear command and control facilities, compromise early warning or firing systems, or even cause the launch of a nuclear weapon has become disturbingly real. While this challenge will impact all nuclear-armed states, it appears particularly acute for the USA and Russia given their large, diverse, and highly alerted nuclear forces. The fact that east–west relations have deteriorated to a nadir perhaps not seen since the 1980s, strategic instability has increased – particularly in the wake of the Ukraine and now Syria crises – and that the nuclear arms reductions agenda appears to have reached a standstill makes this challenge particularly pressing. In this discouraging milieu, new cyberthreats are both exacerbating the already strained US–Russia strategic balance – particularly the perceived safety and security of nuclear forces – and at the same time creating new vulnerabilities and problems that might be exploited by a third party. Taken together, these dynamics add another major complication for current arms control agreements and possible future nuclear cuts, and also seem likely to increase the possibility of accidents, miscalculation, and potential unauthorised nuclear use, especially given the large number of nuclear weapons that remain on "hair-trigger" alert.